A Qualitative Meta-Synthesis of the Challenges Perceived by Nurses in Home Health Nursing - Wang, Lingli; Qin, Yi; Wang, Chenhui; Chen, Tianxi; Gu, Yuhui; Ji, Yunlan (Journal of community health nursing, 2023)
To aggregate and synthesize the findings of qualitative studies exploring the challenges perceived by nurses in home health nursing. A qualitative meta-synthesis. A comprehensive search of multiple databases was conducted in December 2020 and updated in October 2022. Data were analyzed using the meta-aggregation method, and the analytical process used to derive themes was inductive. Eleven qualitative studies were included, and four major challenges perceived by nurses were identified: (1) challenges in the performance of duties, (2) struggles with specific and restricted factors related to practice, (3) underestimation of the value of emotion, and (4) a difficult-to-surmount relationship gap. Home health nursing is associated with numerous challenges due to its complexity and high demand. The findings of this study are beneficial with respect to obtaining a deeper understanding of the challenges associated with home nursing. After considering the existing problems, it is necessary to take measures to overcome these challenges, and individuals, families and society should make efforts to develop this profession further.